Structural Characteristics of the Government in Iran after the Islamic Revolution - Heidar Shahriari (دولت‌پژوهی, 2019)
Characteristics of state in Iran has attracted some of political scientists’ attraction since past times; therefore, various theories, including Patrimonial, Neo-Patrimonial, Sultanism, Absolutism, Rentier, Quasi-Modernity, Eastern Despotism, etc., have been proposed to examine the characteristics and features of contemporary states in Iran. Most of the theories about the features of the state in contemporary Iran are mainly general, theoretical and qualitative, each dealing with the characteristics of the state in contemporary Iran from a particular angle or point of view. Contrary to other theories and works, which are largely general and based on the levels of theoretical analysis, the present paper seeks to begin with the question of what constituted the structural features of government after the Islamic Revolution (until the early 1990s). In this regard, this paper attempts to respond to this by proposing a case study of the relationship between the growth of the new middle class and the process of democracy development in Iran after the Islamic Revolution, on one hand, and the role of the state in influencing this relationship on the other hand. The process and findings of this survey, which are mainly exploratory and structured, show that the government in Iran after the Islamic Revolution has both rentier and ideological features.